NDRG1 Activity in Fat Depots Is Associated With Type 2 Diabetes and Impaired Incretin Profile in Patients With Morbid Obesity - Stafeev, Iurii; Sklyanik, Igor; Mamontova, Elizaveta; Michurina, Svetlana; Shestakova, Ekaterina; Yah’yaev, Kamil; Yurasov, Anatoliy; Masnikov, Denis; Sineokaya, Maria; Ratner, Elizaveta; Vorotnikov, Alexander; Menshikov, Mikhail; et al. (Frontiers in Endocrinology, 2021)
Objective: We aimed to investigate insulin-, mTOR- and SGK1-dependent signaling basal state in morbidly obese patient's fat. We analyzed correlations between signaling activity, carbohydrate metabolism and incretin profiles of patients. Methods: The omental and subcutaneous fat was obtained in patients with obesity. The omental study included 16 patients with normal glucose tolerance (NGT) and 17 patients with type 2 diabetes mellitus (T2DM); the subcutaneous study included 9 NGT patients and 12 T2DM patients. Insulin resistance was evaluated using hyperinsulinemic euglycemic clamp test and HOMA-IR index. Oral glucose tolerance test (OGTT) for NGT patients and mixed meal tolerance test (MMTT) for T2DM patients have been performed. The levels of incretins (GLP-1, GIP, oxyntomodulin) and glucagon were measured during the tests. Signaling has been analysed by Western blotting in adipose tissue biopsies. Results: We have shown equal levels of basal phosphorylation of insulin- and mTOR-dependent signaling in omental fat depot in NGT and T2DM obese patients. Nevertheless, pNDRG1-T346 was decreased in omental fat of T2DM patients. Correlation analysis has shown inverse correlation of pNDRG1-T346 in omental fat and diabetic phenotype (HbA1c, impaired incretin profile (AUC GLP-1, glucagon)). Moreover, pNDRG1-T346 in subcutaneous fat correlated with impaired incretin levels among obese patients (inverse correlation with AUC glucagon and AUC GIP). Conclusions: According to results of the present study, we hypothesize that phosphorylation of pNDRG1-T346 can be related to impairment of incretin hormones processing. pNDRG1-T346 in adipose tissue may serve as a marker of diabetes-associated impairments of systemic incretin profile and insulin sensitivity.